A randomized controlled trial of a new treatment for labor dystocia. (2nd September 2018) - Wiberg-Itzel, Eva; Wray, Susan; Åkerud, Helena
Abstract: Objective: Labor dystocia is an intransigent, high-profile issue in obstetric care. Amniotic fluid lactate (AFL) reflects the uterine metabolic status. High levels associate with subsequent need for operative intervention due to dystocia. In sports medicine, it is known that lactic acid can affect muscular performance and can be decreased by bicarbonate given orally before physical activity. Material and methods: Two hundred dystocic deliveries were included. At the confirmation of dystocia, the AFL-level was analyzed. Deliveries were randomized to an intake of bicarbonate or not. In the "non-bicarbonate-group", stimulation with oxytocin was started immediately. In the "bicarbonate-group", bicarbonate was given; and oxytocin was started 1 hour after the intake. New sampling of AF was performed after 1 hour in both groups. Outcome measured: if an oral intake of bicarbonate changes the AFL levels and enhances delivery outcome in dystocic deliveries. Results: Bicarbonate decreases the AFL levels ( p < .001). The spontaneous vaginal delivery rate after treatment with bicarbonate was increased ( p = .007), without affecting the fetal outcome. Conclusions: An increase of spontaneous vaginal deliveries resulted from bicarbonate ingestion by dystocic women. A decreased level of AFL-level was shown. This simple, low cost treatment has the potential to improve maternal morbidity and satisfaction worldwide.